Incidence of postoperative pain after use of calcium hydroxide mixed with normal saline or 0.2% chlorhexidine digluconate as intracanal medicament in the treatment of apical periodontitis - Ifeoma Nkiruka Menakaya; Olabisi Hajarat Oderinu; Ilemobade Cyril Adegbulugbe; Olufemi Peter Shaba (Saudi Dental Journal)
Objective: To compare the incidence of postoperative pain after the use of calcium hydroxide powder mixed with normal saline or 0.2% chlorhexidine digluconate as intracanal medicament. Participants: Fifty-five subjects aged 17–60 years with teeth diagnosed to have apical periodontitis. Intervention: Two-visit conventional root canal treatment of seventy teeth. The teeth were divided by randomization (balloting) into two groups: control group and experimental group, each with thirty-five teeth treated with calcium hydroxide mixed with normal saline or with 0.2% chlorhexidine digluconate as intracanal medicament respectively. Incidence of postoperative pain was assessed using the universal pain assessment tool and whether or not analgesic was taken. Main outcome measured: Incidence of post-operative pain. Result: Postoperative pain occurred only at 1-day and 1-week reviews. In the control group, the overall incidence of pain was the same at both review periods (5.7%), while the experimental group showed a slight decrease in incidence between 1-day (17.2%) and 1-week (11.4%) reviews. Incidence of flare-ups was more in the experimental group (11.4%) than in the control group (5.7%). No significant statistical differences between the two groups were observed (p > 0.05). Conclusion: The incidence of postoperative pain was lower in the normal saline treatment group, but the difference was not statistically significant. Keywords: Apical periodontitis, Calcium hydroxide, Chlorhexidine, Normal saline, Postoperative pain, Root canal treatment